Respiratory complications in the early post-operative period following elective craniotomies - Bharati, Sachidanand J.; Pandia, Mihir P.; Rath, Girija P.; Bithal, Parmod K.; Dash, Hari H. (Journal of Neuroanaesthesiology and Critical Care, 2015)
Background and Aims: Respiratory complications are of major concern after intracranial procedures. The objective of the study was to assess the incidence of respiratory complications in the initial 72 hours after elective craniotomies and to identify the associated risk factors. Materials and Methods: Patients undergoing elective craniotomies were studied prospectively. Information pertinent to history, physical examinations, investigation reports, perioperative events and outcome at discharge of the patients were recorded. Occurrence of any sign or symptom of respiratory system, need for reintubation/increased ventilatory support within 72 hours of surgery were considered as post-operative respiratory complication. Relationships of numerical variables and categorical variables with post-operative respiratory complications (PRCs) were assessed via T test and Chi-square (or Fisher’s exact). Multivariate analysis using multiple logistic regression was performed for finding independent risk factors for respiratory complications. Results: Out of 961 patients, 137 (14.3%) patients developed PRC within 72 hours of surgery. Ninety-nine (10.3%) patients developed purulent tracheobronchitis. The patients who had PRC had longer hospital stays and poor Glasgow Outcome Scale at hospital discharge. The variables found as independent risk factors were tachycardia, blood transfusion in the intraoperative period and Glasgow Coma Scale (GCS) deterioration, hypokalemia and fever in the post-operative period. Conclusions: Respiratory complications within first 72 hours of elective craniotomies were common and were associated with prolonged hospital stay and poor neurological outcome. The variables which were found as independent risk factors were tachycardia, blood transfusion in the intraoperative period and GCS deterioration, hypokalemia and fever in the post-operative period.
Keywords: Acute respiratory distress syndrome; craniotomy; intracranial procedures; pneumonia; respiratory complications; tracheobronchitis